Animal welfare and human ethics: A personality study - Konstanze Albrecht; Florentin Krämer; Nora Szech (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
We elicit concern for animal welfare in an incentivized, direct and real setup that allows us to separate genuine interest in animal welfare from confounding factors like advertisement, replacement arguments or image concerns. Subjects choose between intensive farming and organic living conditions for a laying hen. Opting for better living conditions is costly, but guarantees better food, daylight, and more space to the hen. Hence subjects have to trade off a selfish benefit (money) against the welfare of a hen. Our data shed light on a long-standing philosophical debate about the relationship between animal welfare and human ethics. We confirm that subjects with higher interests in the hen's well-being exhibit higher moral standards towards humans. Supporters of intensive farming are significantly less prosocial and open-minded, and more Machiavellian than others.
Keywords: D01; D62; D69; 330; Animal welfare; human ethics; experiment; sustainability